1991
DOI: 10.1038/sc.1991.1
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of cerebral blood flow in patients with orthostatic hypotension after spinal cord injury

Abstract: Summ aryTwo groups of patients who developed orthostatic hypotension (OH) after spinal cord injury (SCI) were studied. In the first group all patients (4 females and 6 males) were asymptomatic, whereas in the second group (1 female and 9 males) all had clinical manifestations of hypotension. All but 3 patients were tetraplegic , and these patients were paraplegic above the T6 level. For this study blood pressure (BP) , heart rate and cerebral blood flow (CBF) velocity were measured simultaneously on a tilt tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 10 publications
0
45
0
3
Order By: Relevance
“…In SCI patients with tetraplegia, a decline in blood pressure during tilting was associated with symptoms only in those individuals in whom cerebral blood flow was reduced to low levels. 81 Indeed, in this study, cerebral blood flow was significantly lower in individuals with symptomatic orthostatic hypotension (32.575 cm/s) compared to asymptomatic individuals (40.978 cm/s, Po0.02), even though the decrease in blood pressure with postural change was similar in the two groups (Figure 4). These investigators suggested, therefore, that autoregulation of cerebral blood flow, rather than systemic blood pressure, plays the dominant role in the apparent adaptation to orthostatic hypotension in SCI patients.…”
Section: Cerebral Autoregulationmentioning
confidence: 48%
See 2 more Smart Citations
“…In SCI patients with tetraplegia, a decline in blood pressure during tilting was associated with symptoms only in those individuals in whom cerebral blood flow was reduced to low levels. 81 Indeed, in this study, cerebral blood flow was significantly lower in individuals with symptomatic orthostatic hypotension (32.575 cm/s) compared to asymptomatic individuals (40.978 cm/s, Po0.02), even though the decrease in blood pressure with postural change was similar in the two groups (Figure 4). These investigators suggested, therefore, that autoregulation of cerebral blood flow, rather than systemic blood pressure, plays the dominant role in the apparent adaptation to orthostatic hypotension in SCI patients.…”
Section: Cerebral Autoregulationmentioning
confidence: 48%
“…These investigators suggested, therefore, that autoregulation of cerebral blood flow, rather than systemic blood pressure, plays the dominant role in the apparent adaptation to orthostatic hypotension in SCI patients. However, it is remarkable that such low pressures (approximately 85/60 mmHg) 81 should be tolerated. If the systemic blood pressure decreases to low levels, the cerebral perfusion pressure (in the upright position) will be reduced considerably further, due to the hydrostatic effect of the height difference between the head and heart when upright.…”
Section: Cerebral Autoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hypotensive manifestations may be present for several months, until patients develop tolerance to the low blood pressure. 3 Although it has been reported that the pathogenesis of orthostatic hypotension caused by SCI is complex and involves the cardiovascular, renal, neurological and the endocrine systems, the true cause is uncertain. 4,23 Our data demonstrated that compression and tilting increased the sensitivity of resistant arteries to Ach and the increased sensitivity was more marked in animals administered with SM-SOD during compression and tilting.…”
Section: Discussionmentioning
confidence: 99%
“…15,18 Moreover, the slowing of extent of the cerebral blood¯ow as shown by the transcranial Doppler technique, does not correlate with the data given by the tensiometer but with the clinical symptoms of OH, demonstrating that the autoregulation of the cerebral blood¯ow is preserved. 21 Although OH is common in those who are tetraplegic, it does not appear in every such individual. One may wonder why: An answer could be that incomplete lesions of the autonomic nervous system may exist, similar to incomplete motor and sensory lesions but we do not have the means of detecting these clinically.…”
mentioning
confidence: 99%